GIS-based Valuation of Ecosystem Services in Mountain Regions: A Case Study of the Chepelare Municipality in Bulgaria - Ivanova, Ekaterina; Koulov, Boian; Borisova, Bilyana; Assenov, Assen; Vassilev, Kiril (European Journal of Sustainable Development, 2016)
This study imports the Ecosystem Services concept in the economic valuation of the resources of a typical mountain municipality in Bulgaria. It applies a GIS-based approach and employs a system of methods, which include benefit transfer, market price, and contingent valuation, as well as local survey and statistical data for the following key ecosystem services: timber production, forest/agricultural products, and tourism and recreation. The investigation interprets the CORINE Land Cover (2012) classes as spatial units of identification, analysis, and valuation of selected Ecosystem Services, on which the welfare of local mountain population depends. Its results, among which is a map of the total economic value of a set of ecosystem services in the Municipality of Chepelare, is intended to support sustainable local governance in mountain regions. Key words: ecosystem services valuation, sustainable governance, GIS, mountain regions, Bulgaria.